Synthesis and characterization of nanoparticles of Nico Alloy @Au Core-Shell Structure - Nguyen, Ngoc Minh (2007)
The objective of the study is to produce a narrow size distribution via various parameters such as concentration of metallic ions, reducing agent, surfactant and molecular weight of surfactant. Results obtained for NiCo alloy nanoparticles showed that the molecular weight of surfactant has the most significant effect on the particle size and its distribution (in range of value from 4.7 to 7.01 nm) compared to the other parameters studied in this work.